Diaspora Civil Society: The Nexus of Civil Society, Soft Power and Foreign Policy - Abubakar, Yusuf Wara; Islam, MD. Nazmul (Journal of Applied And Theoretical Social Sciences, 2025)
Introduction: This article analyzes the connection between Civil Society, Soft Power and Foreign Policy in the rubrics of international politics. The link between the concepts hinges on the fact that while civil societies are being used as foreign policy tools, the latter is considered a significant beneficiary of the former. Moreover, as foreign policy becomes a component of soft power, the latter posits a persuasive approach to the former. Method: This research adopts concept mapping methods to explain the mutual relationships among the three concepts. By extracting pertinent articles from the Web of Science database and creating a map, we examine and provide the foundation of our article that there are relationships among the three notions. Results or Findings: The research found out that the trio concepts have symbiotic relations, which work in unison to promote a nation’s interest. Within these relations we concludes that Civil Society is increasingly becoming relevant as a tool in foreign affairs. Discussion or Conclusion: In the post-COVID-19 era, civil societies have emerged as influential actors not only in domestic governance but also in advancing foreign policy objectives through soft power. Their growing involvement demonstrates the interconnection between civil society, soft power, and foreign policy. By complementing state diplomacy with cultural, humanitarian, and developmental initiatives, civil societies reinforce national influence abroad. This synergy illustrates how these three dimensions collectively enhance a nation’s global image and strategic interests in contemporary international relations.